1993
DOI: 10.5271/sjweh.1472
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic evaluation of muscular work pattern as a predictor of trapezius myalgia.

Abstract: VEIERSTED KB, WESTGAARDRH, ANDERSEN P. Electromyographic evaluation of muscular work pattern as a predictor of trapezius myalgia. Scand J Work En viron Health 1993;19:284-90. Electromyographic (EMG) measurements and interviews concerning muscular pain and disability were performed prospectively every 10th week on 30 healthy new female employees of a chocolate manufacturing plant. The static muscle activity and rate of short unconscious interruptions in EMG activity (EMG gaps) of the trapezius muscle during rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
178
3
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(193 citation statements)
references
References 23 publications
10
178
3
2
Order By: Relevance
“…As previously presented by Veiersted et al (1993), lack of muscle rest periods is a plausible risk factor for development of WMSDs. Due to the cross-sectional design of the present study, it cannot be stated whether the cases showed less muscle rest than controls also before the complaints developed.…”
Section: Muscle Restmentioning
confidence: 56%
See 2 more Smart Citations
“…As previously presented by Veiersted et al (1993), lack of muscle rest periods is a plausible risk factor for development of WMSDs. Due to the cross-sectional design of the present study, it cannot be stated whether the cases showed less muscle rest than controls also before the complaints developed.…”
Section: Muscle Restmentioning
confidence: 56%
“…Due to the cross-sectional design of the present study, it cannot be stated whether the cases showed less muscle rest than controls also before the complaints developed. Veiersted et al (1993) showed that the number of short muscle rest periods were significantly lower for the patients, also before patient status. Moreover, a prospective study of light manual workers in the poultry and fish industries showed higher mean shoulder muscle EMG activity both prior to and after the start of complaints among workers who later developed neck/shoulder complaints presented, compared with workers who stayed healthy (Madeleine et al, 2003).…”
Section: Muscle Restmentioning
confidence: 85%
See 1 more Smart Citation
“…A muscular activity pattern with almost no EMG gaps may be crucial, as it has been shown that few EMG gaps may be related to the development of work-related musculoskeletal symptoms (23). One of the mechanisms behind this relationship may be an association between EMG gaps and the rotation of motor unit recruitment (24), which thus possibly prevents the overload of muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective field study of repetitive industrial work, the muscle activity pattern had predictive value (15). Some studies show no unambiguous associations between EMG data and disorders (16,17).…”
mentioning
confidence: 99%